Lean management and performance of telecommunication firms: The mediating role of workplace structure - A. P. Afunwa; E. K. Agbaeze; N. M. Ike; E. E. Isichei (Cogent Business & Management, 2020)
The need to improve the performance of the telecommunication sector in Nigeria was the major motivation for this study. The study relied on requisite literature to provide a relative understanding of the concepts. Survey design was used and a sample of 299 employees across 6 state offices of selected telecommunication firms was used. Stratified sampling technique was adopted for selecting participants for the study. Partial least square SEM was used for data analysis with the aid of Smartplsv3.9. The study found that lean management practices have a significant effect on performance of telecommunication firms. The study also found that workplace structure mediates the relationship between lean management practices and performance in the telecommunication sector. The study recommends the need for structuring the workplace to allow for smooth implementation and practising of lean activities, as it is beneficial towards improving the performance of the telecommunication firms.
Keywords: 650; Lean management; workplace structure; performance and telecommunication